Good-genes effects in sexual selection - ller, A. P. M (1999)
The magnitude of the effect of good genes as a viability benefit accruing to choosy females remains a controversial theoretical and empirical issue. We collected all available data from the literature to estimate the magnitude of good-genes viability effects, while adjusting for sample size. The average correlation coefficient between male traits and offspring survival in 22 studies was 0.122, which differed highly significantly from zero. This implies that male characters chosen by females reveal on average 1.5% of the variance in viability. The studies demonstrated considerable heterogeneity in effect size; some of this heterogeneity could be accounted for by differences among taxa (birds demonstrating stronger effects), and by differences in the degree of mating skew in the species (high skew reflecting stronger effects). Although these results suggest that viability-based sexual selection is widespread across taxa, they indicate that the effect is relatively minor. Finally, there was also an effect of publication year in that the more recent studies reported reduced effects. This may reflect publication biases during paradigm shifts of this debated issue, but it should also be recalled that the studies have only partly estimated the full fitness consequences of mate choice for offspring.